STATUS DEMOTION IN LOYALTY PROGRAM: STRATEGY FOR CLOSE TO THE THRESHOLD CUSTOMERS - Igamo, Altamim Marie; Afiff, Adi Zakaria (ASEAN Marketing Journal, 2021)
Manuscript type: Documentary Research. Research Aims: Identifying loyalty program strategies to demoted closed to the threshold customers with additional points and additional time in own money and other money customer to have positive evaluate toward program’ and company’ loyalty intention. Design/methodology/approach: This research employs 2 (payment source: own money vs other money) × 3 (demotion strategies: without additional point vs with additional points vs with additional time) factorial designs between-subject. Research Findings: Loyalty intention to the loyalty program appear stronger with demotion strategies with an additional point and additional time than demotion without additional point Theoretical Contribution/Originality: Enrich references about the status of demotion in HLP, distributive justice in the context of loyalty programs and scarcity theory in marketing. Practitioner/Policy Implication: Marketing managers should concern more about the strategy to demoted customer, especially customer who close to the threshold to produce more positive consumer evaluation. Research limitation/Implications: Further studies can focus on participant that have used airline loyalty programs to have stronger external validity.